Comparing clinical performance of current implantable cardioverter-defibrillator implantation recommendations in arrhythmogenic right ventricular cardiomyopathy. Issue 2 (2nd September 2021) - Bosman, Laurens P; Nielsen Gerlach, Claire L; Cadrin-Tourigny, Julia; Orgeron, Gabriela; Tichnell, Crystal; Murray, Brittney; Bourfiss, Mimount; van der Heijden, Jeroen F; Yap, Sing-Chien; Zeppenfeld, Katja; van den Berg, Maarten P; Wilde, Arthur A M; et al.
Abstract: Aims: Arrhythmogenic right ventricular cardiomyopathy (ARVC) patients have an increased risk of ventricular arrhythmias (VA). Four implantable cardioverter-defibrillator (ICD) recommendation algorithms are available The International Task Force Consensus ('ITFC'), an ITFC modification by Orgeron et al. ('mITFC'), the AHA/HRS/ACC guideline for VA management ('AHA'), and the HRS expert consensus statement ('HRS'). This study aims to validate and compare the performance of these algorithms in ARVC. Methods and results: We classified 617 definite ARVC patients (38.5 ± 15.1 years, 52.4% male, 39.2% prior sustained VA) according to four algorithms. Clinical performance was evaluated by sensitivity, specificity, ROC-analysis, and decision curve analysis for any sustained VA and for fast VA (>250 b.p.m.). During 6.4 [2.8–11.5] years follow-up, 282 (45.7%) patients experienced any sustained VA, and 63 (10.2%) fast VA. For any sustained VA, ITFC and mITFC provide higher sensitivity than AHA and HRS (94.0–97.8% vs. 76.7–83.5%), but lower specificity (15.9–32.0% vs. 42.7%-60.1%). Similarly, for fast VA, ITFC and mITFC provide higher sensitivity than AHA and HRS (95.2–97.1% vs. 76.7–78.4%) but lower specificity (42.7–43.1 vs. 76.7–78.4%). Decision curve analysis showed ITFC and mITFC to be superior for a 5-year sustained VA risk ICD indication threshold between 5–25% or 2–9% for fast VA. Conclusion: The ITFC and mITFC provide the highest protection rates, whereas AHA and HRS decrease unnecessary ICD placements. ITFC or mITFC should be used if we consider the 5-year threshold for ICD indication to lie within 5–25% for sustained VA or 2–9% for fast VA. These data will inform decision-making for ICD placement in ARVC.